'Well-being paradox' revisited: a cross-sectional study of quality of life in over 4000 adults with congenital heart disease. Issue 6 (22nd June 2021) - Andonian, Caroline Sophie; Freilinger, Sebastian; Achenbach, Stephan; Ewert, Peter; Gundlach, Ulrike; Hoerer, Jürgen; Kaemmerer, Harald; Pieper, Lars; Weyand, Michael; Neidenbach, Rhoia Clara; Beckmann, Jürgen
Abstract : Objective: The present cross-sectional study investigated quality of life (QOL) in a large cohort of German adults with congenital heart disease (ACHDs) in association with patient-related and clinical variables. Design: Cross-sectional survey. Participants: Between 2016 and 2019, a representative sample of 4014 adults with various forms of congenital heart defect (CHD) was retrospectively analysed. Inclusion criteria were confirmed diagnosis of CHD; participant aged 18 years and older; and necessary physical, cognitive and language capabilities to complete self-report questionnaires. Primary and secondary outcome measures: QOL was assessed using the 5-level EQ-5D version (EQ-5D-5L). Sociodemographic and medical information was obtained by a self-devised questionnaire. Associations of QOL with patient-reported clinical and sociodemographic variables were quantified using multiple regression analysis and multiple ordinal logit models. Results: Overall, ACHDs (41.8±17.2 years, 46.5% female) reported a good QOL comparable to German population norms. The most frequently reported complaints occurred in the dimensions pain/discomfort (mean: 16.3, SD: p<0.001) and anxiety/depression (mean: 14.3, p<0.001). QOL differed significantly within ACHD subgroups, with patients affected by pretricuspid shunt lesions indicating the most significant impairments (p<0.001). Older age, female sex, medication intake and the presence of comorbidities were associated with significant reductions in QOL (p<0.001). CHD severity was positively associated with QOL within the dimensions of self-care (OR 0.148, 95% CI 0.04 to 0.58) and mobility (OR 0.384, 95% CI 0.19 to 0.76). Conclusion: Current findings temper widely held assumptions among clinicians and confirm that ACHDs experience a generally good QOL. However, specific subgroups may require additional support to cope with disease-related challenges. The negative correlation of QOL with age is especially alarming as the population of ACHDs is expected to grow older in the future. Trial registration number: DRKS00017699; Results.